MONTESQUIEU DAN MAKNA SEBUAH KEADILAN - Daya Negri Wijaya (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
People face many injustice practices at present. This will be a national concern. Justice which should be guaranteed by the standing law does not execute as common. Montesquieu concerns on the justice and law. Government should look at a law as an independent power from the executive power. Therefore, law should be fitted with the concrete situation of a nation and should not be following the authority’s will. Montesquieu with his justice spirit inspires the way of revolution. He makes an analogy of king and pope as the liars. They place people as a duping object. He is also claimed as one of philosophers in France. This paper will discuss the meaning of justice and its relation to the spirit of revolution.